BILANGAN KROMATIK LOKASI UNTUK JOIN DARI DUA GRAF - Yuli Erita (Jurusan Matematika FMIPA Universitas Andalas Padang, 2013)
Let f be a proper k-coloring of a connected graph G and = (V) bean ordered partition of V (G) into the resulting color classes. For a vertex v of G, thecolor code of v with respect to is dened to be the ordered k-tuplec(v) = (d(v; V1); d(v; V2); :::; d(v; V));where d(v; Vi) = minfd(v; x)jx 2 Vikg, 1 i k: If distinct vertices have distinct colorcodes, then f is called a locating coloring. The minimum number of colors needed in alocating coloring of G is the locating chromatic number of G, and denoted by (G). Inthis paper, we study the locating chromatic number of the join of some graphs.